(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
We conducted a comprehensive clinical and laboratory examination of 60 vaccinated patients, aged 18 to 70 years, with a confirmed diagnosis of "COVID-19 in vaccinated patients." We established the clinical diagnosis of patients on the basis of epidemiological anamnesis, clinical examination and laboratory results. The mean age of the patients was 50.3±2.83; males predominated by gender. The peculiarity of the clinical course of "COVID-19" was characterized by the predominance of a moderate course of the disease and the absolute predominance of the contact-household factor in maintaining a high level of morbidity. The majority of deaths from COVID-19 have been among the elderly and those with chronic comorbidities, and deaths have been reported among people of all ages. In addition, the pandemic has caused increased morbidity and required the introduction of measures to control it, which has adversely affected the economies of countries around the world. The global response to the pandemic to develop various vaccines to protect against COVID-19 is unprecedented in public health history. The issue of COVID-19 vaccination is the most pressing issue in the medical community today.